MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MA DENGAN MENGGUNAKAN PENDEKATAN OPEN ENDED - Nugraha, Agung; Mulyana, Irpan; Hutajulu, Masta; Sugandi, Asep Ikin (IKIP Siliwangi, 2019)
AbstractThis research is based on the problem of the low mathematical problem solving ability of students who have a relationship with someone's success in solving a problem that they face. In this case, to overcome this, a class of research was conducted using an open ended approach and ordinary learning. In addition, this research is a quasi-experimental. The population in this study were students of class X MA in Bandung in 2018/2019 academic year. The research sample is all Class X students in one MA in Bandung. Quantitative analysis was performed using the two-difference test and descriptive qualitative analysis was also carried out. The results showed that the ability to solve mathematical problems using the open ended approach was better than those using the usual approach.